Analysis of Flipbook Mathematics Learning Media in Improving Students' Critical Thinking Skills - Ariyanto, Yuyun; Akhyar, Muhammad; Efendi, Agus (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This research and development study aims to determine the condition of students' critical thinking skills in mathematics learning and analyze the effectiveness of the results of developing flipbook-based mathematics learning modules in improving critical thinking skills. This research method uses the RnD approach, namely research carried out by developing flipbook-based learning modules. The development procedure model adapts the Borg and Gall development model, 1) research and data collection; 2) Implementation of planning 3) development of original products; 4) conducting initial field trials; 5) Check the original product; 6) conducting limited field trials; 7) making other product versions; 8) conducting functional field tests; 9) Check the final product; and 10) carrying out production and implementation.The determination of the subject used the Simple Random Sampling technique, which is taking samples from the population randomly without considering the strata in the population. The subjects of this study were 83 students from the pretest and posttest classes. Based on the results of the study, the conditionsMathematics learning at SMA MTA Surakarta, many students have difficulty developing critical thinking skills. Students feel bored and uninterested in following mathematics lessons, because there is no variation in learning (monotonous). In addition, it turns out that there are no modules that can be used by teachers and students other than LKS. In the needs analysis, it was discovered that students and teachers needed a new module that could be applied with current technological advances. The test results showed a t-value of -11.230 and a Sig. (2-tailed) value of 0.000. This can be concluded that there is a significant difference between the pretest and posttest groups. So it can be concluded thatFlipbook-based mathematics learning modules are effective in improving critical thinking skills.